The glacial epoch - Jolly, Fred Ralph (My University, 1895)
Intoduction: A remarkable and stupendous period which followed that one in which the solid portion of the earth was formed was the glacial period. Nothing in geological researches has been more fully proned than the existence of this period, which left its traces in unmistakable monuments over the face of the earth, and written its history upon their ranks.
Citation: Jolly, Fred Ralph. The glacial epoch. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Glacial period; Glacial epoch; Geological; Research; Theses; Manuscripts (documents)